Zwei Diagramme des scheinbaren Ganges der Sonne - Thorn, Karl (ERDKUNDE, 1961)
Many geography undergraduates fail to acquire sufficient knowledge of mathematical geography. It therefore seems desirable to present to them the basic facts in an easily comprehensible illustrative way. This is done here for the course of the sun, first at different latitudes on the days of the summer and winter solstices and second for the entire year at 49° lat. The diagrams are drawn as simple cylindrical projections (plate carrée). The height above the horizon is used as ordinate, the azimuth as abscissa. Lines of equal time interval from true noon make it possible to read off the time from half hour to half hour. On the first diagram a series of important phenomena can be demonstrated, e. g. midnight sun, length of day and dusk, culmination of the sun for certain latitudes and times in the north, etc. The second diagram illustrates the degree of insolation of surfaces for any degree of slope and any aspect, and further permits comparison of these with each other both with and without inclusion of the insolation values.